Efecto del tiempo en la fertilidad de huevos de gallinas criollas (Gallus gallus domesticus)” - Murillo Suárez, Milton Absalon (2012)
The present investigation had for object to determine the effect of the time in the fertility of eggs of Creole hens (Gallus gallus domesticus). The investigative work was carried out in the canton Guano, parish San Isidro, county of Chimborazo, in the property of Mr. Milton Absalon Murillo Suárez. The incubation was carried out under internal conditions of temperature and controlled relative humidity. Ambient temperature 130C, 50% of relative humidity, heliophany 1.460 hours of average yearly and 2.780 m.s.n.m. The design experimental employee was a D.B.C.A. with 10 treatments and 3 repetitions, the taking of data was made to the 21 days of incubation, to which were carried out the statistical analysis by means of Statistical Analysis System (SAS). The procedure ANOVA was used for the variance analysis and the test of Tukey (0,05). He was also carried out an economic analysis of each treatment in study, estimating the cost of production. Of the results he settles down that the best treatments are the T1 (Incubation to 1 day after the posture), T2 (Incubation to 2 days after the posture), T3 (Incubation to 3 days after the posture), T4 (Incubation to 4 days after the posture) and T5 (Incubation to 5 days after the posture); because they reach a percentage from birth from 80% to 100% in incubation of eggs of Creole hen. The treatments T2 (Incubation to 2 days after the posture), T3 (Incubation to 3 days after the posture) and T4 (Incubation to 4 days after the posture) they presented the smallest cost of production with a value of U$D 0,46 and the treatment T10 (Incubation to 10 days after the posture) it presented the biggest value in U$D 3,44 of cost of production. To reach from birth between 80 and 100% in incubation of eggs of Creole hens (Gallus gallus domesticus), it is recommended to incubate eggs from the 1 to the 5 day after the posture.